Pengaruh Limited Time Offer Dan User Experience Terhadap Keputusan Pembelian Melalui Aplikasi McDonald’s Di Cikupa Kabupaten Tangerang - Shiva Fauziah; Agung Wijoyo (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to examine the effect of limited time offers and user experience on purchasing decisions through the McDonald's application in Cikupa Kabupaten Tangerang. The research method used is quantitative. The sampling technique uses the Slovin formula and obtained a sample of 100 respondents. Data analysis was carried out by testing validity, reliability, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis tests. The results showed that limited time offers had a significant effect on purchasing decisions with a determination coefficient of 49.0% and the hypothesis test obtained a Tcount value > Ttable (9.707 > 1.984). User experience also had a significant effect with a determination coefficient of 69.4% and the hypothesis test obtained a Tcount value > Ttable (14.891 > 1.984). Simultaneously, limited time offer and user experience have a significant effect on purchasing decisions with the regression equation Y = 1.998 + 0.303X1 + 0.498X2 and a coefficient of determination of 75.5%, while the remaining 24.5% is influenced by other factors outside this study. The simultaneous test (F test) shows Fcount > Ftable (149.772 > 3.090), so the research hypothesis is accepted